Analisis Pengaruh Lingkungan Kerja terhadap Kinerja Pegawai dengan Gaya Kepemimpinan sebagai Variabel Moderasi pada Kantor BPPKAD Kabupaten Sampang - Nasim Nasim; M. Isa Anshori (Trending: Jurnal Manajemen dan Ekonomi, 2024)
The objectives of this research are: (1) To analyze the importance of the influence of the work environment on the performance of BPPKAD Sampang Regency employees. (2) There is no significant influence of leadership style on employee performance at BPPKAD Sampang Regency. (3) Analysis of the significance of the influence of the work environment moderated by leadership style on the performance of BPPKAD Sampang Regency employees. The population used in this research was all BPPKAD Sampang Regency employees, totaling 96 people. The data collection technique uses a questionnaire that has passed validity and reliability tests. Test the regression conditions using classic hypothesis testing. The data analysis technique uses multiple regression analysis with an absolute difference test, and hypothesis testing is carried out using the t test. The results of this research show that: 1) The work environment has a significant influence on employee performance at BPPKAD Sampang Regency. Therefore, the following hypothesis is important: 2) Leadership style has a significant influence on employee performance at BPPKAD Sampang Regency. Therefore, the following hypothesis is important: 3) Management style cannot/has not been proven to reduce the impact of the work environment on the performance of BPPKAD Sampang Regency employees.